Analisis Lingkungan Kerja terhadap Stres dan Kinerja Karyawan di Distributor Plafon PVC Gemolong - Ela Rosalinda; Anniez Rachmawati Musslifah; Faqih Purnomosidi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This qualitative study investigates how the work environment influences employee stress levels and performance at a PVC ceiling distribution company in Gemolong. A comfortable and supportive workplace is considered essential in fostering employee productivity, while unmanaged stress can hinder work outcomes. The research adopts a case study approach, gathering data through in-depth interviews with five current employees, complemented by direct observation and document analysis. Results indicate that both the physical layout and social dynamics of the workplace significantly shape employees’ perceptions and behaviors. Positive environmental conditions—such as cleanliness, mutual support, and safety—help reduce stress and enhance work quality. In contrast, unclear roles, workplace noise, and poor communication were commonly associated with increased stress and decreased performance. The study recommends that the company pay attention to improving both tangible and intangible elements of the work environment to support employee well-being and maintain performance standards.